Penerapan Keterampilan Proses Sains pada Mata Pelajaran IPA terhadap Keaktifan Peserta Didik di MTs Muhammadiyah Parumaan - Alkahfi Alkahfi; Dian Ernaningsih; Fitriah Fitriah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Increasing student learning activity needs to use a learning model. In a lesson there are methods that are used systematically which become a unified procedure in the delivery of learning material so that the learning objectives are achieved. This study aims to determine the application of science process skills in science subjects to the activeness of students at MTs Muhammadiyah Parumaan. This research uses a descriptive method with a qualitative approach. This descriptive research method is used because it relates to the topics and problems that will be discussed, namely the application of science process skills in science subjects to the activeness of students at MTs Muhammadiyah Parumaan. The learning activity of VII B students at MTs Muhammadiyah Parumaan was based on the results of the supervision of the school principal when the teacher taught classes using conventional methods, not all students had active learning during the learning process. Researchers apply learning with science process skills. The results showed that the application of process skills to class VII B students at MTs Muhammadiyah Parumaan experienced an increase from the low category to the medium category